Empirical Analysis of Social Factors Research on Economic Development: The Case of Georgia - Asie Tsintsadze; Vladimer Glonti; Merab Diasamidze; Tamar Ghoghoberidze (Communications of International Proceedings, 2024)
The primary objective of the socially oriented economy in the context of the market economy is to facilitate the social protection of all societal strata and to formulate an effective social policy. A greater proportion of the populace is subjected to social assistance in the absence of an effective social system. People lose the motivation to engage in effective economic activity when economic growth is not met by an improvement in their well-being. The labour force is the primary resource; however, the challenges associated with its reproduction impede the advancement of economic and social well-being. The objective of this paper is to investigate the role of the demographic structure in the development of economic well-being. This will reveal the factors that influence the socio-economic situation and create the potential for the application of these approaches in the implementation of social policy. The change in the demographic structure will result in a decrease in the number of individuals seeking social assistance, and financial resources will be allocated to the economy's growth. Scientific research rarely addresses the causes of the demographic transition disruption, which impedes the advancement of the socio-economic situation. A regression analysis was conducted to determine the influence of the factors affecting the demographic dividend, and conclusions were drawn about the asymmetry between the factors hindering the demographic transition and the economic development ul attitude. The demographic dividend is estimated using the demographic dividend calculation algorithm, which is adjusted by the adjustment coefficient K calculated by the ratio of the pension amount and per capita expenses. The country will be able to reduce its dependence on external financing and increase the proportion of domestic investments in economic development by activating the identified factors. Consequently, a portion of the government's funds will be directed abroad.
Keywords: economic development; demographic dividend; workforce; welfare; social policy.